2016
DOI: 10.4067/s0301-732x2016000100014
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour, tympanic temperature and performance of dairy cows during summer season in southern Chile

Abstract: RESUMENEl objetivo del estudio fue evaluar los efectos de las condiciones climáticas del verano sobre la producción de leche, actividad animal y temperatura timpánica (TT; n = 15), utilizando variables climáticas y tres índices de comodidad térmica. Los datos se analizaron considerando hora del día y categorías del índice comprensivo del clima (CCI). Se estimaron modelos de regresión simple para predecir la tasa de respiración (RR) de las vacas (α = 0,05). Los índices termales fueron normales y pobres predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 16 publications
5
18
0
4
Order By: Relevance
“…A summary of the major behavioural responses includes changes on feeding, defecating and urinating frequency, water intake, lying time, standing time, shade seeking behaviour (Ratnakaran et al 2017). In addition, body temperature as well behaviour has been affected by heat stress (Jara et al 2016, Tucker et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the major behavioural responses includes changes on feeding, defecating and urinating frequency, water intake, lying time, standing time, shade seeking behaviour (Ratnakaran et al 2017). In addition, body temperature as well behaviour has been affected by heat stress (Jara et al 2016, Tucker et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Esto permite señalar que el aumento de la TT observada después de las 17:00 h (Figura 2) no estaría asociada a las variables meteorológicas imperantes en el momento del transporte, sino más bien al transporte en sí. Lo anterior basado en que las diferencias de magnitud TT reportadas previamente en la literatura no superan los 0,5 °C en ese mismo horario (Arias et al, 2011;Jara et al, 2016). En este caso en particular, la diferencia de magnitud observada fue de 1,6 °C.…”
Section: Discussionunclassified
“…El valor mínimo se observó temprano en la mañana (37,50 y 37,86 °C, para tratamientos 1,85 y 2,72 veces EMm, a las 08:00 y las 07:00 h, respectivamente), mientras que el valor máximo se observó durante la tarde (38,58 y 40,03 °C, para tratamientos 1,85 y 2,72 veces EMm, respectivamente, ambos a las 18:00 h). Estos resultados son consistentes con otros estudios que reportan ritmos y valores similares Mader y Johnson, 2010;Gaughan y Mader, 2013;Jara et al, 2016). Cabe señalar que los valores promedios de TT también varían según la época del año y el tipo de dieta (energía) consumida por los animales (Arias et al, 2011), pero siempre manteniendo un ritmo circadiano.…”
Section: Discussionunclassified
“…Tympanic temperatures (TT) were measured in beef cattle through data loggers placed in the ear canal [ 81 , 82 , 83 ]. This method was also used in dairy cows to measure heat strain [ 84 , 85 ]. However, several limitations may affect its further application in practice.…”
Section: Detection Of Heat Strain Based On the Most Commonly Used Animal-based Indicatorsmentioning
confidence: 99%
“…Myers and Henderson [ 89 ] found that TT readings were lower than RT consistently in both Holstein calves and cows. Jara et al [ 85 ] reported that the TT of 15 multiparous Holstein-Friesian dairy cows was highly associated with thermal indices, especially with the comprehensive climate index (CCI). However, no threshold was given in this study.…”
Section: Detection Of Heat Strain Based On the Most Commonly Used Animal-based Indicatorsmentioning
confidence: 99%